2017
DOI: 10.23865/nof.v31.579
|View full text |Cite
|
Sign up to set email alerts
|

Å kommunisere en konflikt – aktører i RTs dekning av situasjonen i Ukraina i februar–mars 2014

Abstract: Communicating Conflict: Actors in RT Coverage of the Situation in Ukraine FebruaryÁMarch 2014This article analyses the Russian public diplomacy news organization RT's coverage of the situation in Ukraine in FebruaryÁMarch 2014, the period that culminated with the annexation of Crimea. It finds that enemy images were drawn of the West/USA and of Ukrainian radicals, whereas the liberal opposition and in part the new Ukrainian government were subjected to «symbolic annihilation» Á that is they were not represente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…Our analysis of the articles on RT International's website found that their framing of the conflict in Ukraine was strikingly similar to the narrative of President Putin. This corresponds well with other observations of the network (Hutchings et al, 2015;Østevik, 2017).…”
Section: Policiessupporting
confidence: 93%
See 1 more Smart Citation
“…Our analysis of the articles on RT International's website found that their framing of the conflict in Ukraine was strikingly similar to the narrative of President Putin. This corresponds well with other observations of the network (Hutchings et al, 2015;Østevik, 2017).…”
Section: Policiessupporting
confidence: 93%
“…strikingly similar to the narrative of President Putin. This corresponds well with other observations of the network (Hutchings et al, 2015;Østevik, 2017). Hence, the Russian state had 'arrested the war' and used RT International to spread its strategic narrative and achieve legitimacy for its actions among an international audience.…”
Section: Policiessupporting
confidence: 89%
“…These studies point out that the conflict in Ukraine has reinforced pre-existing anti-Western narratives in Russian political and media discourse. Also emphasised is the recurrent enemy image of Ukrainian radicals found in Russian coverage of the conflict (Hansen 2015;Hutchings and Szostek 2015;Gaufman 2017, 103-123).The Russian leadership uses such narratives strategically to legitimise its behaviour in the eyes of the public and to strengthen the image of Russia as a great power (Ostevik 2017;Szostec 2017a,b). However, Hutchings and Szostec (2015, 194) note that "the visceral anti-western rhetoric is not as undifferentiated as is often suggested", and that Russia still wishes to position itself as a European nation.…”
Section: Introductionmentioning
confidence: 99%